Evaluating labour market interventions - O?Neill, Donal (Statistical and Social Inquiry Society of Ireland, 2000)
The high growth rates experienced in Ireland over the last 10 years has resulted in a tightening of the labour market which is reflected in the number of unfilled vacancies reported by firms. At the same time wage inequality has increased leading to greater demands being placed on the government to tackle social exclusion. In response to these issues, recent governments have proposed a range of policies involving direct intervention in the labour market. Effective implementation of these policies requires careful monitoring and evaluation of their effects. This paper examines the procedures currently available for evaluating labour market interventions. The results of recent evaluations of minimum wages laws, reform of the benefit system and changes in working-time conditions are used to illustrate the methodologies involved. The paper also describes the data requirements of these methodologies and examines the currently available Irish labour market data in this light.
Barrington Lecture 1999/2000
Read before the Society, 30 March 2000
Keywords: Programme evaluation; Social experiments; Labour market; 314.15